"Patients with amyotrophic lateral sclerosis (ALS) are usually nice persons"—How physicians experienced in ALS see the personality characteristics of their patients. Issue 1 (10th November 2016) - Mehl, Theresa; Jordan, Berit; Zierz, Stephan
Abstract: Introduction: Physicians experienced in the treatment of patients with amyotrophic lateral sclerosis (ALS) occasionally describe these patients as "nice" persons. Methods: ALS experienced physicians ( n  =   36) were asked to assess the personality characteristics of ALS patients using a multidimensional personality questionnaire based on the five‐factor model of personality. Control groups consisted of physicians experienced in Myasthenia gravis (MG) ( n  =   21) and lung cancer (LC) ( n  =   36). Results: In the dimension Agreeableness ALS patients were rated significantly higher than the other groups ( p  <   .001). This was mainly due to the high scores for converse adjective pairs "stubborn—compliant" and "selfish—helpful". Discussion: The dimension Agreeableness is very similar to "niceness". Results support the anecdotal description of ALS patients as "nice" persons. Personality characteristics of ALS patients differentiate them from other patient groups. It remains open whether the "nice" personality structure is linked to the susceptibility to the disease. Abstract : The main objective was to analyze the personality structure of amyotrophic lateral sclerosis (ALS) patients assessed by experienced physicians. The reason for this investigation was the predominant anecdotal descriptions of these patients as very "nice" and "warm" persons compared to other patient groups. As a main result, we showed that there is a similar personality characteristic common to patients with ALS that differentiate them from other patient groups. This personality dimension is quite similar to the concept of "niceness".